2022
DOI: 10.1177/03010066221091729
|View full text |Cite
|
Sign up to set email alerts
|

Face masks have a limited influence on first impressions: evidence from three experiments

Abstract: Considering the widespread use of face masks during the COVID-19 pandemic, the goal of the current study was to examine how occlusion of the lower half of the face may impact first impression formation. We conducted three experiments, each building on previous research, investigating the effect of face masks on first impressions of faces across the lifespan (children, young and older adults). Experiment 1 examined whether the mandatory influence of happy facial expressions on perceived trustworthiness in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Thus, it might be that when asked to make trustworthiness and approachability judgments of angry faces, there may be no difference between masked versus unmasked faces, unlike what is found here when happy faces were used. A recent study (Twele et al, 2022 ) had explored this to a certain extent with a focus on trustworthiness; further work is still needed particularly on approachability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be that when asked to make trustworthiness and approachability judgments of angry faces, there may be no difference between masked versus unmasked faces, unlike what is found here when happy faces were used. A recent study (Twele et al, 2022 ) had explored this to a certain extent with a focus on trustworthiness; further work is still needed particularly on approachability.…”
Section: Discussionmentioning
confidence: 99%
“…Although past research has investigated the influence of masks on person perception, these studies have focused on only a few traits and the results have been mixed. For example, some studies related to predominantly White targets have found no evidence for the impact of masks on perceived trustworthiness (Grundmann et al., 2021; Twele et al., 2022) or competence/dominance (Oldmeadow & Koch, 2021), while other studies have demonstrated a positive impact of masks on trustworthiness (Fang & Kawakami, under review; Oldmeadow & Koch, 2021; Olivera‐La Rosa et al., 2020) and competence (Fang & Kawakami, under review). Yet other studies have found a negative impact on trustworthiness (Malik et al., 2021) and competence (Twele et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a rating study by Biermann et al (2021) , masked faces were evaluated as less trustworthy and less happy than unmasked faces; however, this effect was attenuated in participants who experienced high psychological distress and risk perception associated with the pandemic, and who showed high compliance with prevention measures to avoid infection. In a set of experiments, Twele et al (2022) pointed out that facial masks might have a limited impact in forming first impressions of unfamiliar faces from across the lifespan. Specifically, they found that young adult faces with happy expressions were rated as more trustworthy than neutral faces, even when the same face had been previously seen with a mask; and that the presence of masks does not affect the adult’s perceived niceness of childs’ faces and the trustworthiness and competence of older adults face.…”
Section: Introductionmentioning
confidence: 99%